Vertical flow constructed wetland: a technological innovation for domestic wastewater treatment at Paoay Lake, Municipality of Paoay, Ilocos Norte, Philippines - Batin, Charlie B; Pablico, Julius R; Agtarap, Jacob A; Bonuen, Karen Joy G; Teneza, Justine Rose A; Achuela, Amabel H (International Journal of Biosciences and Biotechnology, 2023)
Wastewater has been a major problem for various communities in the Philippines and worsens as the human population trends upward. Paoay Lake, a water body in the northernmost of the country, is not an exception to this problem. It is one of the country’s largest natural lakes and the region’s largest and most accessible freshwater for domestic use. The lake is also used for recreation and ecotourism activities. However, with the growing domestic and agricultural sectors, the already contaminated lake is receiving more wastewater generated by households and farming practices; thus termed domestic wastewater. This research sought to introduce a vertical flow constructed wetland (VFCW) as a technological innovation for domestic wastewater treatment at Paoay Lake, Municipality of Paoay, Ilocos Norte, Philippines. It specifically aimed to (1) determine the socio-demographic profile of the communities around the lake; (2) determine the lake’s physical, biological, and hydrological characteristics based on the available data; (3) introduce vertical flow constructed wetlands for domestic wastewater treatment; and (4) calculate the flow rate of water extraction by the local households to determine the design and dimension of the wastewater treatment facility. Secondary data were used to achieve the first two objectives, which further revealed the lake’s poor water quality. Thus, the introduction of wastewater treatment facilities such as VFCW is deemed very effective and efficient in treating domestic wastewater while considering the lake’s overall characteristics during the planning and design; the VFCW can be replicated for other water bodies in the Philippines